Peningkatkan Hasil Belajar Pkn melalui Penerapan Metode Demonstrasi dan Tanya Jawab pada Siswa Kelas V SDN Ponjanan Timur 1 Batumarmar Pamekasan - Samsir Noor Alamsyah (Departement of Mathematics Education, 2023)
The ability to design programs concerns the teacher's ability to formulate learning objectives, convey subject matter, choose and use learning methods, utilize and use media and learning resources, and carry out evaluations. Then the skill of communicating the program concerns the skills of the teacher in conveying learning material to students. This study aims 1) to find out how to improve the learning outcomes of Citizenship Education about the Unitary State of the Republic of Indonesia through the application of demonstration and question and answer methods to fifth grade students at SDN Ponjanan Timur 1, Batumarmar District, Pamekasan Regency. 2) To find out the results of learning Citizenship Education about the Unitary State of the Republic of Indonesia through the application of the demonstration method and question and answer in class V SDN Ponjanan Timur 1, Batumarmar District, Pamekasan Regency. The research used was PTK. The implementation of CAR refers to the CAR cycle model by Kemmis and Taggart which includes four stages, namely 1) planning, 2) implementing actions, 3) observing, and 4) reflecting. The results showed that: 1) The effectiveness of demonstration and question and answer methods can improve the ability to learn Citizenship Education about the Unitary State of the Republic of Indonesia in grade V students. 2) Students' understanding of the Unitary State of the Republic of Indonesia increased in cycle II compared to cycle I. Improved results Student learning is caused by the teacher optimizing the application of demonstration and question and answer methods which are supported by the use of learning media in the form of pictures and group discussions in learning activities. 3) The application of demonstration and question and answer learning methods can increase motivation and develop independent initiatives and attitudes, and can deepen students' knowledge. The ability to design programs concerns the teacher's ability to formulate learning objectives, convey subject matter, choose and use learning methods, utilize and use media and learning resources, and carry out evaluations. Then the skill of communicating the program concerns the skills of the teacher in conveying learning material to students. This study aims 1) to find out how to improve the learning outcomes of Citizenship Education about the Unitary State of the Republic of Indonesia through the application of demonstration and question and answer methods to fifth grade students at SDN Ponjanan Timur 1, Batumarmar District, Pamekasan Regency. 2) To find out the results of learning Citizenship Education about the Unitary State of the Republic of Indonesia through the application of the demonstration method and question and answer in class V SDN Ponjanan Timur 1, Batumarmar District, Pamekasan Regency. The research used was PTK. The implementation of CAR refers to the CAR cycle model by Kemmis and Taggart which includes four stages, namely 1) planning, 2) implementing actions, 3) observing, and 4) reflecting. The results showed that: 1) The effectiveness of demonstration and question and answer methods can improve the ability to learn Citizenship Education about the Unitary State of the Republic of Indonesia in grade V students. 2) Students' understanding of the Unitary State of the Republic of Indonesia increased in cycle II compared to cycle I. Improved results Student learning is caused by the teacher optimizing the application of demonstration and question and answer methods which are supported by the use of learning media in the form of pictures and group discussions in learning activities. 3) The application of demonstration and question and answer learning methods can increase motivation and develop independent initiatives and attitudes, and can deepen students' knowledge.